2010
DOI: 10.1080/0972060x.2010.10643814
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the Volatiles ofCitrus macropteravar.annamensisand Evaluation of Bioactivity

Abstract: The distillation and subsequent extraction of the distillate obtained from the fresh peels of the fruits of Citrus macroptera var. annamensis afforded 120 mg of oil (yield 0.12 %). Analyses both by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS) of the sample resulted in the identification of 25 terpenoids, predominantly monoterpene hydrocarbons, accounting for 97.0 % of the total oil, and limonene (73.5 %) as the major component. While the oil did not exhibit any in vitro free-radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(18 reference statements)
2
5
1
Order By: Relevance
“…Table 2 showed the list of individual compounds identified in the spectra. The compounds identified were comparable to volatile components reported from other Citrus fruits [13,14,17,19] .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Table 2 showed the list of individual compounds identified in the spectra. The compounds identified were comparable to volatile components reported from other Citrus fruits [13,14,17,19] .…”
Section: Resultssupporting
confidence: 75%
“…As expected, the specific gravity of the fixed oil (0.982) was found to be higher than the specific gravity for the extracted essential oil (0.692 and 0.671, respectively for fresh and dried peels). The yield of essential oil from fresh peels of C. macroptera fruits was comparable to the yield of 0.12 % reported from Bangladesh [17] and lower than 0.53 % reported from Manipur, India [14] .…”
Section: Resultssupporting
confidence: 56%
“…Swingle (family: Rutaceae), commonly known as 'lime', cultivated extensively in tropical and subtropical countries mainly for its use as a food item or food additive, is also medicinally best known throughout the world as a remedy that relieves fevers, sore throat, coughs, common cold and indigestion (Fukumoto et al, 2006;Dr Duke's Phytochemical and Ethnobotanical Databases, 2010;GRIN Taxonomy Database, 2010). As part of our continuing phytochemical and pharmacological studies on Citrus species (Sarker et al, 2008;Miah et al, 2010), this is a report on the assessment of the effects of lime (C. aurantifolia) essential oils in preventing ketotifen-induced weightgain in mice. hence it was necessary to assess the essential oil further using GC-MS (Fukumoto et al, 2006;Nguyen et al, 2009;Razavi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While previous bioactivity studies on this plant revealed its analgesic, anti-infl ammatory, antimicrobial, anti-oxidant, antimalarial, antihepatotoxic activities, and antidiarrheal and wound-healing properties (Umachigi et al, 2007;Alam et al, 2008a,b), the phytochemical investigations resulted in the isolation of indole alkaloids, secoiridoids, triterpenes and saponins from this plant (Banerji, 1977;1978;Brown & Chapple, 1976;Kitagawa et al, 1996;Sahu et al, 1999;. In continuation of our phytochemical and pharmacological screening of Bangladeshi medicinal plants (Uddin et al, 2005(Uddin et al, , 2007aDatta et al, 2007;Nayeem et al, 2006;Saha et al, 2007;Alam et al, 2008a,b;Mazid et al, 2009;Ara et al, 2010;Miah et al, 2010), we report on the hypoglycemic and oxidative stress-reducing activities of the hydroethanolic extract of the flowering tops of A. cadamba in alloxan-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%